Antichronic Gastric Ulcer Effect of Zinc-Baicalin Complex on the Acetic Acid-Induced Chronic Gastric Ulcer Rat Model - Hui Yang; Yi Lu; Xiao-Feng Zeng; Ling Li; Rong-Ping Zhang; Zhong-Kun Ren; Xu Liu (Gastroenterology Research and Practice)
Background. Baicalin (BA) has been shown to have anti-inflammatory and antioxidant activity. Zinc is a nutrient element. Objective. This study is aimed at investigating the antichronic gastric ulcer activity of Zn-Baicalin complex (BA-Zn) and its related mechanisms in an acetic acid-induced gastric ulcer rat model. Results. The severely ulcerated gastric mucosa of model rats had lower GSH-Px (52.21 ± 7.13) and SOD (7.03 ± 0.10) activity, and higher MDA (2.39 ± 0.03) content compared to sham rats. BA-Zn reduced the gastric ulcer index in a dose-dependent manner, significantly increased SOD activity and GSH-Px level, and reduced the MDA content and IL-8 and TNF-α levels in the gastric mucosa. BA-Zn (6.5 and 13 mg/kg) exerted a greater antiulcerogenic effect than both BA and zinc-gluconate, leading to a reduced ulcer index (18.43 ± 1.11, 15.00 ± 1.44), decreased MDA content (1.33 ± 0.07, 0.63 ± 0.01), and increased SOD activity (17.62 ± 0.11, 20.12 ± 0.32) and GSH-Px levels (102.12 ± 9.11, 120.25 ± 9.07). In addition, our results from Western blot suggested that BA-Zn (6.5 and 13 mg/kg) has a greater antiulcerogenic effect than both BA and zinc-gluconate. Conclusion. The BA-Zn complex possesses greater antichronic gastric ulcer properties compared to BA and zinc-gluconate due to its ability of oxidation resistance and anti-inflammatory effects.